Path and Mechanism of Blockchain Embedded in Innovation Management of Cultural and Creative Industrial Park - Huilan Wei; Shunfeng Guan (Discrete Dynamics in Nature and Society)
As a new business form of Cultural and Creative Industrial Cluster, the management of Cultural and Creative Industrial Park is faced with many difficulties, such as imperfect credit mechanism, lagging efficiency of intellectual property management, difficulties in industrial chain integration and upgrading, and imperfect development evaluation system. The “decentralization” concept of blockchain 3.0 technology can provide guidance value for the management concept innovation of Cultural and Creative Industry Park, and the embedding of technologies such as “smart contract”, “distributed ledger”, and “digital currency” can promote the construction of “programmable management system of Cultural and Creative Industry Park”. According to the analysis path of architecture, function system, and application scenario of park management, this paper constructs the architecture from consensus layer, network layer, and data layer, constructs the function system from the public chain, alliance chain, and private chain, and locates the application scenario from the dimensions such as industrial chain management and government supervision and management; thus, the direction and focus of management innovation of blockchain 3.0 technology embedded in Cultural and Creative Industry Park are clarified. The research results of this paper have good theoretical guidance for the management subjects of Cultural and Creative Industry Park (local government, park management committee, industry organizations, etc.) to determine the path of implementing management innovation by using blockchain 3.0 and to build a scientific park management mechanism.